Pemberdayaan Ekonomi Masyarakat Islam Berbasis Masjid (Studi Kasus Pemberdayaan Yatim Masjid Ar Rahmah Surabaya) - Mauludi Mauludi; Muh Syahril Sidik Ibrahim; Muhammad Rifaid; Ahmad Faiz Khudlari Thoha (Alhadharah: Jurnal Ilmu Dakwah, 2023)
In the actualization of proselytizing bil hal, economic empowerment becomes a concrete step. Economic Empowerment is a strategic step to alleviate poverty. This research raises how mosques carry out orphan empowerment with the perspective of proselytizing bil hal. The purpose of this study is to find out how the implementation of da'wah bil hal through the orphan empowerment program organized by the Ar Rahmah Perak Mosque in Surabaya. This research uses a qualitative approach. Data collection techniques are carried out through, observation, interviews, and document studies. The collected data are analyzed with a Grounded theory Analysis. The results of this study show the strategic role of mosques in breaking the chain of poverty through the empowerment of orphans. The Empowerment Program is packaged in a comprehensive and long-term oriented strategy, including compensation and fulfillment of daily needs, educational scholarships up to the undergraduate level as well as efforts to provide jobs for orphans' mothers. The results of this study can be useful as an alternative model for poverty alleviation in Indonesia as a form of proselytizing bil hal inner mosque. This research also emphasizes the social function of mosques as centers of people's problems.